The Legal Aspect of the National Education Budget Allocation - Achmad Syauqy (Yuridika, 2018)
Education is part of the constitutional rights owned by the citizens and should be fulfilled by the State. Better proportion of educational budgetting will expand the access of education for the citizens.  Article 31 Paragraph 4 of the 1945 Constitution explicitly states the number of 20 percent of the fulfillment of the education budget as a guarantee of citizens’ educational rights. Nevertheless, the implementation of the aforementioned provision has been interpreted in various policies.  This research answers the issue of law aspect regarding the implementation of educational budget allocation nationally. This is a doctrinal research with different approaches namely: statute, conceptual, and case. In this research, three important things are concluded: (1) The constitutional framers were lack of comprehend consideration in formulating provision related to educational budget. (2) The inconsistency of several principles such as the principle of Justice, Principle of Efficiency, Principle of Transparency, Principles of Public Accountability, and Principle of Effectiveness in the educational budget policy (3) Ineffectivity of administrative sanction since it has no significant effects to the substantial aspect of education equality and its improvement. The research offers several solutions (1) Constitutional amendment on the provision of educational budget allocation provided with reliable academic papers. (2) Designs effective supervision mechanism towards the local public budgeting (APBD) (3) Open the access for public participation.